Tuning the size and surface of InP nanocrystals by microwave-assisted ionic liquid etching - Siramdas, Raghavender (Kansas State University, 2018)
Semiconductors are materials whose conductivity is between metals and insulators. Semiconductor nanocrystals (NCs) have sizes in the range 2 to 10 nm. Because of their unique optical properties like tunable emission wavelength, narrow emission peak, and stability over dyes, they have potential applications in displays. Indium phosphide (InP) is considered a less toxic alternative to commercially used cadmium-based semiconductor NCs. Microwave-assisted (MA) methods using ionic liquids (ILs) afford fast reaction heating rates because of the good MW absorbing capacity of ILs. For tuning size and surface, which are some of the important problems associated with the InP NCs, new synthetic methods are reported herein. In MAIL etching HF generated in the microwave reaction etches the InP NCs surface. Pyridinium and imidazolium based ILs containing tetrafluoroborate (BF₄⁻) and hexafluorophosphate (PF₆⁻) ions yield luminescent NCs. In a silicon carbide (SiC) reaction vessel, which blocks most of the microwaves penetrating into the reaction, bigger NCs form than those from a Pyrex reaction vessel because of the higher reaction temperatures in the SiC vessel. By changing microwave set-power (SP), different reaction times can be achieved. Though a small degree of change in average NC diameter of the NCs is observed at different SPs and reaction temperatures, addition of dodecylamine (DDA) yields NCs with average sizes between 3.2 to 4.2 nm with a broad size distribution. At lower SPs smaller NCs form and at higher SPs bigger NCs form. NC luminescence can be tuned from green (545 nm) to red (630 nm) in the visible region with quantum yields as high as 30%. Rapid heating and InP precursor activation might be responsible for the larger change in NC size. The effect of DDA on NC size is also verified by microwave reactions in SiC vessels. ILs containing PF₆⁻ ions at 280 °C will modify the surface of the NCs so the NC dispersibility changes from non-polar (toluene) to polar (DMSO) as the amount of IL increases. This is due to ligand stripping, which is the removal of large palmitic ligands from the NC surface. These NCs have broad absorption features and emission peaks with QYs of up to 30%. Fourier transform infrared spectroscopy indicates the absence of palmitic acid ligands on the NC surface and zeta potential measurements indicate the presence of anions on the NC surface. From X-ray photoelectron spectroscopy and nuclear magnetic resonance spectroscopy, the inorganic ion PO₂F₂⁻ is identified on the NCs surface.
Keywords: InP nanocrystals; Ionic liquid etching; Microwave-assisted method; Photoluminescence; Size and surface